1998
DOI: 10.1111/j.1745-6606.1998.tb00399.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Testing of a Measure of Skepticism Toward Environmental Claims in Marketers' Communications

Abstract: Marketers' claims about the environmental effects of products and their packaging are becoming more pervasive. Consumer organizations, government, and marketers have long realized that consumers receive such claims with some degree of skepticism. An investigation of how consumer skepticism affects the response to “green” marketing claims would be facilitated by a reliable and valid measure of skepticism. This paper describes a two‐stage research project and the resulting four‐item measure of skepticism toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
298
2
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(312 citation statements)
references
References 37 publications
(27 reference statements)
2
298
2
10
Order By: Relevance
“…Whereas internal CSR communication itself will thus rather be perceived as extrinsic, positive external CSR communication should drive attributions to intrinsic motives due to higher levels of credibility and trust (Parguel et al 2011;Becker-Olsen et al 2006). Prior research found that consumers are more likely to have negative attitudes, beliefs, and behaviors toward the organization when they assign extrinsic motives compared to intrinsic motives (Becker-Olsen et al 2006;Ellen et al 2006;Mohr et al 1998;Yoon et al 2006).…”
Section: The Mediating Role Of Motives: Attribution Theorymentioning
confidence: 99%
“…Whereas internal CSR communication itself will thus rather be perceived as extrinsic, positive external CSR communication should drive attributions to intrinsic motives due to higher levels of credibility and trust (Parguel et al 2011;Becker-Olsen et al 2006). Prior research found that consumers are more likely to have negative attitudes, beliefs, and behaviors toward the organization when they assign extrinsic motives compared to intrinsic motives (Becker-Olsen et al 2006;Ellen et al 2006;Mohr et al 1998;Yoon et al 2006).…”
Section: The Mediating Role Of Motives: Attribution Theorymentioning
confidence: 99%
“…Roberts, 1996). A third definition of highly involved green consumers relies on their self-reported green purchase behaviour (Chang, 2011;Mohr et al, 1998;Shrum et al, 1995). These three dimensions of environmental involvement are related but have different antecedents and outcomes.…”
Section: Environmental Involvementmentioning
confidence: 99%
“…The skepticism is more situational and not longer, while the cynicism is enduring and deep [5]. Also, the skepticism is just the doubt about the communication, beside cynicism is not only doubt what is said, but motive for saying something [5] [6].…”
Section: Theoretical Backgroundsmentioning
confidence: 99%
“…The skepticism is more situational and not longer, while the cynicism is enduring and deep [5]. Also, the skepticism is just the doubt about the communication, beside cynicism is not only doubt what is said, but motive for saying something [5] [6]. This study anticipated the higher level of cynicism is a more negative belief and trust of social marketing campaign and then the corporate is focused on benefit by themselves even though they are communicated with consumer in the basis of trust of social marketing [7].…”
Section: Theoretical Backgroundsmentioning
confidence: 99%